4CPS-185 The effectiveness of enzyme replacement therapy in the management of gaucher disease. (March 2019) - Attjioui, H; Cheikh, A; Aliat, Z; Lazrak, M; Bennani, I; Mefetah, H; Bouatia, M
Abstract : Background: Gaucher disease is a rare genetic disorder, due to a deficiency of glucocerebrosidase activity. It is most often manifested by hepatosplenomegaly, haematological and biochemical disorder. First-line treatment is based on enzyme replacement therapy (ERT). Purpose: To evaluate the tolerance and effectiveness of ERT in children with type 1 Gaucher disease. Material and methods: We report the case of four patients with type 1 Gaucher disease treated with ERT (once every 15 days) at the neuro-metabolic diseases unit of our hospital. The evaluation was performed on the basis of primary effectiveness variables (haemoglobin concentration, platelet count, liver parameters) and the reporting of adverse events. Results: There were three girls and one boy, whose clinical signs were manifested by hepatosplenomegaly and haematological disorder in all patients. The ERT had generally been well tolerated and no adverse effects were identified. Conclusion: The ERT used by our patients has an acceptable tolerance profile as well as beneficial effects on the parameters related to the disease. These beneficial effects were demonstrated by the effectiveness variables that were kept stable or improved throughout the treatment in children with Gaucher disease. References and/or acknowledgements: Thanks to the paediatrics department for their support. No conflict of interest.